Retinal Ischemic Perivascular Lesion Reflects Cerebral Small Vessel Disease Burden in Single Subcortical Infarction - William R. Kwapong; Yuying Yan; Le Cao; Hang Wang; Chen Ye; Shuai Jiang; Wendan Tao; Bo Wu (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Retinal ischemic perivascular lesions (RIPLs) are an indicator of ischemia in the middle retina. We aimed to determine the relationship between RIPLs and single subcortical infarction (SSI). We also investigated the differences in cerebral small vessel disease imaging burden between groups with and without RIPLs in SSI. Methods and Results In this case–control study, we enrolled 82 patients with SSI and 72 nonstroke controls. All participants underwent magnetic resonance imaging and swept‐source optical coherence tomography/optical coherence tomography angiography. Small vessel disease markers such as lacunes, cerebral microbleeds, white matter hyperintensity, and perivascular spaces were rated on brain imaging. RIPLs were assessed via swept‐source optical coherence tomography. Optical coherence tomography angiography was used to measure the superficial vascular complex and deep vascular complex of the retina. After adjusting for risk factors, the presence of RIPLs was significantly associated with SSI (odds ratio [OR], 1.506 [95% CI, 1.365–1.662], P<0.001). Eyes with RIPLs showed lower deep vascular complex density (P=0.035) compared with eyes without RIPLs in patients with SSI. After adjusting for vascular risk factors, the presence of RIPLs in patients with SSI was associated with an increased periventricular white matter hyperintensity burden (β=0.414 [95% CI, 0.181–0.647], P<0.001) and perivascular spaces‐basal ganglia (β=0.296 [95% CI, 0.079–0.512], P=0.008). Conclusions RIPLs are associated with SSI independent of underlying risk factors. The relationship between the presence of RIPLs and small vessel disease markers provides evidence that RIPLs might be an additional indicator of cerebral ischemic changes.